2021
DOI: 10.3390/su13147954
|View full text |Cite
|
Sign up to set email alerts
|

Non-Traditional Systemic Risk Contagion within the Chinese Banking Industry

Abstract: Systemic risk contagion is a key issue in the banking sector in maintaining financial system stability. This study is among the first few to use three different distance-to-risk measures to empirically assess the domestic interbank linkages and systemic contagion risk of the Chinese banking industry, by using bivariate dynamic conditional correlation GARCH model on data collected from eight prominent Chinese banks for the period 2006–2018. The results show a relatively high correlation among almost all the ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Future researchers may extend this study by considering the calendar effects in Bitcoin’s conditional volatility that significantly affect its return (Kinateder and Papavassiliou, 2021). Another area of interest might be the contagion risk to other developed or even developing countries (Choudhury and Daly, 2021; Choudhury et al , 2021; Daly et al , 2019; Yoon et al , 2021) as the financial risk during COVID-19 in the Australian stock markets may trigger spillover effects.…”
Section: Discussionmentioning
confidence: 99%
“…Future researchers may extend this study by considering the calendar effects in Bitcoin’s conditional volatility that significantly affect its return (Kinateder and Papavassiliou, 2021). Another area of interest might be the contagion risk to other developed or even developing countries (Choudhury and Daly, 2021; Choudhury et al , 2021; Daly et al , 2019; Yoon et al , 2021) as the financial risk during COVID-19 in the Australian stock markets may trigger spillover effects.…”
Section: Discussionmentioning
confidence: 99%
“…These indicators are widely used by international organizations and financial authorities as well to monitor the risk of financial institutions (Harada et al 2013 ). The seminal work by Merton ( 1973 ) introduced the concept of distance to default (DD) referring to it as the distance between the current market-based position of a financial organization and its hypothetical default position (Fiordelisi and Marqués-Ibañez 2013 ; Choudhury et al 2021 ). It is an inverse measure of a bank’s default risk that means a larger distance between the two or higher value of DD suggests a lower probability of a firm to default.…”
Section: Methodsmentioning
confidence: 99%
“…, 2019). The scholars use various statistical techniques to measure the impact of hard currencies and their long-term association with the global financial system (Choudhury et al., 2021; Kinateder and Wagner, 2014). At the same time, the co-integration largely depends on the period covered, where crises show a higher level of interdependency than moments of general stability.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the co-integration largely depends on the period covered, where crises show a higher level of interdependency than moments of general stability. The financial meltdown of 2008 and the Greek debt crisis of 2011 indicated that financial problems in one country are easily transmitted to others (Choudhury et al., 2021; Seth and Panda, 2018; Boubaker et al., 2016). As a result, national economies are not immune from international developments while interventions often require regional and global initiatives.…”
Section: Introductionmentioning
confidence: 99%